An IoT Based Monkey Deterrent for Plantations with Surveillance System: A Method for Damage Controldone by Monkeys in Plantations - Abdul Rahim, Abdul Muin; Zainal, Mohd Shamian (Progress in Engineering Application and Technology, 2024)
Modern civilization’s rapid growth requires humans to cohabit with other species, notably primates. Many farmers and plantation owners struggle with primates, which undermine crop harvests. The most frequent monkey pest in Malaysia is the Southern Pig-tailed Macaque. This project was created to control monkey damage and deter them from farms and plantation areas. This paper describes an Internet of Things (IoT)-based sound deterrent system. The ESP32 acts a the main controller while ESP32-Cam acts as the surveillance apparatus for the device. This prototype is designed to deter away monkeys while providing a remote method of surveillance paired with ESP32-Cam and PIR sensor.